Polyurethane material with shape memory function, biocompatibility and degradability and preparation method thereof
By introducing degradable structures such as isosorbide, hexahydrotriazine ring and hydroxyethylhexahydrohomotriazine into polyurethane materials, the problem of degradation difficulties of cross-linked polyurethane materials is solved, and high mechanical properties, rapid degradation and Completely decomposed polyurethane materials are suitable for smart materials and environmentally friendly packaging fields.
Patent Information
- Application Number
- CN202411728028.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-28
AI Technical Summary
Crosslinked polyurethane materials have problems of low degradation rate and incomplete degradation in terms of degradation, and the prior art is difficult to achieve controllable rapid degradation and efficient recycling.
By introducing isosorbide and acid-sensitive hexahydrotriazine rings based on bio-based raw materials into the molecular structure of polyurethane materials, combining hydroxyethylhexahydrohomotriazine and polyester polyol, a shape memory function and biodegradable Compatible and degradable polyurethane materials.
It realizes the high mechanical properties, rapid degradation and complete decomposition capabilities of polyurethane materials, can be completely degraded in an acidic environment in a short time (such as 2.2 hours), and has good biocompatibility and shape memory functions.
Smart Images

Figure CN119463091A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of degradable functional polyurethane materials, and in particular to a polyurethane material with shape memory function, biocompatibility and degradability and a preparation method thereof. Background Art
[0003] For the sustainable development of the environment, the preparation of polyurethane products using green polyols, which is currently emerging, is one of the effective means to alleviate the resource crisis. However, the preparation of polyurethane materials, especially cross-linked polyurethane materials, only relies on biomass raw materials instead of petroleum-based raw materials. There are problems such as low degradation rate and incomplete degradation in terms of degradation. This is due to the stability of the carbamate bond and the chemical cross-linking network in the polyurethane product, which makes the degradation of cross-linked polyurethane materials relatively difficult. The degradation of polyurethane is mainly achieved by the chemical decomposition of the carbamate bond in the skeleton, including alcoholysis, hydrolysis, acidolysis, pyrolysis, aminolysis, etc. These degradation methods usually require harsh conditions, such as strong acid / alkali environment under high temperature and pressure, and the degradation rate is difficult to control, and the degradation is incomplete, and may be accompanied by the production of toxic byproducts. Therefore, introducing a degradable structure into the polyurethane molecular chain to achieve controllable degradation and efficient recycling of the material is an effective way to solve the difficulty of degradation of cross-linked polyurethane materials from the source.
[0004] Introducing a degradable structure into the molecular structure can solve the problem of polyurethane material degradation. The patent "A high mechanical performance degradable polyurethane material and its synthesis method" (CN118878782A) discloses that polylactic acid and diisocyanate are used to prepare a degradable polyurethane material with good performance, but no clear degradation time is mentioned. Starting from the perspective of molecular structure design, the present invention develops a polyurethane material with a series of characteristics such as high mechanical strength, shape memory function and degradability based on the hexahydrotriazine ring acidolysis strategy, realizing the sustainable development of polyurethane materials.
[0005] The disclosure of the above background technology content is only used to assist in understanding the inventive concept and technical solution of the present invention. It does not necessarily belong to the prior art of this patent application. In the absence of clear evidence that the above content has been disclosed on the filing date of this patent application, the above background technology should not be used to evaluate the novelty and creativity of the present application. Summary of the invention
[0006] The purpose of the present invention is to propose a polyurethane material with shape memory function, biocompatibility and degradability and a preparation method thereof, so as to solve the problems of degradability and sustainability and expand its application by giving it multifunctionality.
[0007] In order to solve the above technical problems, the present invention has the following technical solutions:
[0008] A polyurethane material with shape memory function, biocompatibility and degradability, wherein the polyurethane structure contains isosorbide based on bio-based raw material, two degradable structures hydroxyethyl hexahydro-s-triazine and polyester polyol; the strength and toughness of the polyurethane material can be regulated by the soft segment structure and molecular weight, and the ratio of soft and hard segments, and the synthesis reaction process is as follows:
[0009]
[0010] The unique three-arm structure of the rigid hexahydrotriazine ring and isosorbide give the material a higher crosslinking density and tensile strength, while the acid-sensitive hexahydrotriazine ring enables the material to have degradation performance.
[0011] The present invention also provides a method for preparing a polyurethane material having shape memory function, biocompatibility and degradability, characterized in that it comprises the following steps:
[0012] (1) taking a certain amount of isosorbide and hydroxyl-terminated polyether or polyester polyol, placing them in a three-necked flask, heating and melting them under a nitrogen atmosphere, and uniformly mixing them, adding a diisocyanate monomer dissolved in a solvent to the mixed liquid, reacting to obtain a viscous liquid, and adding an appropriate amount of solvent to control the viscosity of the reaction system;
[0013] (2) adding hydroxyethyl hexahydro-s-triazine to the polymerization system of step (1), stirring and mixing, and then pouring the reaction mixture into a polytetrafluoroethylene mold to level it;
[0014] (3) placing the mold in an oven to volatilize the solvent and solidify the mold to obtain a polyurethane material having shape memory function, biocompatibility and degradability.
[0015] Furthermore, the hydroxyl-terminated polyether or polyester polyol described in step (1) includes one or more of hydroxyl-terminated poly(1,4-butylene adipate) (PBA), polyethylene glycol (PEG), polypropylene glycol (PPG), polytetramethylene ether glycol (PTMEG), poly(butylene succinate) (PBS), and polylactic acid (PLA), and its molecular weight is 1000-3000.
[0016] Furthermore, the diisocyanate described in step (1) includes one or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), and isophorone diisocyanate (IPDI).
[0017] Furthermore, in step (1), the group ratio NCO:OH is 1.2:1.
[0018] Furthermore, the solvent described in step (1) includes one or more of tetrahydrofuran (THF), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and N-methylpyrrolidone (NMP).
[0019] Furthermore, the conditions for adding the diisocyanate monomer in step (1) are to react at a temperature of 120° C. for 10 hours.
[0020] Furthermore, the stirring and mixing time in step (2) is 30 minutes.
[0021] Furthermore, in step (3), the temperature for solvent volatilization and solidification is 40-100°C.
[0022] Furthermore, the curing time in step (3) is 12 hours.
[0023] Furthermore, the polyurethane material prepared by the present invention contains polar groups such as carbamate structures and ester bonds, which are easy to form intermolecular hydrogen bonds and enhance the interaction between molecular chains.
[0024] Compared with the prior art, the present invention has shown significant progress and unique advantages in multiple dimensions, which are specifically reflected in the following aspects:
[0025] (1) In terms of material composition and performance improvement, the present invention cleverly introduces rigid hexahydrotriazine ring and isosorbide as synergistic factors. This innovative design enhances the overall mechanical properties of the material. This structural optimization enables the polyurethane material of the present invention to exhibit higher strength and toughness when subjected to external forces, and its comprehensive performance surpasses many similar patented products that have been disclosed. It is particularly worth mentioning that the material exhibits excellent rapid degradation characteristics in an acidic environment and can be completely decomposed in a short time. This is undoubtedly a major technological breakthrough in today's increasingly stringent environmental protection requirements.
[0026] (2) In the exploration of the application of smart materials, a major highlight of the polyurethane material of the present invention is its unique shape memory function. This feature enables the material to automatically adjust its shape according to environmental changes under specific temperature conditions. Specifically, in a high temperature environment, the soft segment of the material is in an amorphous state, and the molecular chains are free to rearrange, thereby allowing the shape to change freely; and when the temperature drops to a certain threshold, the deformation-induced molecular chain orientation effect begins to appear, the molecular movement is restricted, and the temporary shape is firmly maintained. This intelligent response mechanism opens up broad prospects for the application of materials in the fields of smart wearables and adaptive structures, and demonstrates a major advancement in the field of materials science and engineering.
[0027] (3) In terms of the diversity of degradation mechanisms, the polyurethane material of the present invention has also achieved significant innovation. The acid-sensitive hexahydrotriazine ring in the material gives it the ability to quickly and completely degrade under specific conditions (such as 50°C, 2 mol / L phosphoric acid / ethanol solution), and complete degradation can be achieved in only 2.2 hours, which is of great significance for application scenarios that require precise control of degradation time. In addition, the polyester segment structure embedded in the material gives the material the function of biodegradation, which means that under the action of specific enzymes, the material can also be partially degraded, greatly reducing the risk of environmental pollution. The design of this composite degradation mechanism not only improves the environmental properties of the material, but also makes it possible for its wide application in the fields of medical implants, environmentally friendly packaging materials, etc., marking an important leap in the field of sustainable development materials.
[0028] In summary, the polyurethane material of the present invention has achieved remarkable progress in mechanical properties, intelligent response and degradation mechanism through a series of innovative designs, and has also injected new vitality into the development of materials science, indicating that it will play an immeasurable role in multiple high-tech fields in the future. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of the typical structure of PBA-based polyurethane.
[0030] Figure 2 FTIR graphs of PBA-based polyurethane films with different soft segment molecular weights.
[0031] Figure 3 The stress-strain curves of PBA-based polyurethane films with different soft segment molecular weights.
[0032] Figure 4 is the shape memory fixation rate (R f ) and recovery rate (R r )picture.
[0033] Figure 5 Fluorescence microscopy images of L929 cells after co-culture with PBA-based polyurethane films for 24h, 48h and 72h.
[0034] Figure 6 This is a graph showing the degradation phenomenon of PBA-based polyurethane films with different soft segment molecular weights in 2 mol / L phosphoric acid / ethanol solution.
[0035] Figure 7 These are digital images of the PBA-based polyurethane series films after 6 weeks of enzymatic hydrolysis and the acid hydrolysis phenomenon. DETAILED DESCRIPTION
[0036] The present invention will be further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be emphasized that the following description is merely exemplary and is not intended to limit the scope of the present invention and its application. The advantages and all changes that can be thought of by relevant technical personnel in the field are included in the present invention, and the present invention covers all modifications, substitutions, equivalent methods and schemes carried out within the concept and scope of the present invention as defined by the claims. The preparation process, reaction conditions, reagents, experimental methods, etc. for implementing the present invention, except for the contents specifically involved below, are all common knowledge and common sense in the art, and the present invention has no specific limiting contents. In order for the present invention to be better understood by the public, some specific details are described in detail here, and for those skilled in the art, the present invention can be fully understood without these details.
[0037] Non-limiting and non-exclusive embodiments will be described with reference to the following figures, wherein like reference numerals refer to like parts unless otherwise specifically stated.
[0038] Example 1
[0039] 2g of hydroxyl-terminated poly (1,4-butylene adipate) (PBA) with a number average molecular weight of 1000 and 0.30g of isosorbide (ISO) were added to a three-necked flask with a stirrer, heated to 60°C, and vacuum-dried for 40min under stirring. Then, 1.2g of hexamethylene diisocyanate (HDI) dissolved in N, N-dimethylformamide (DMF) was added to the mixture, and the mixture was heated to 120°C and continued to react for 10h. At the same time, a certain amount of N, N-dimethylformamide (DMF) was added to adjust the viscosity of the system to form a prepolymer. 0.3g of hydroxyethyl hexahydro-s-triazine (HT) was added to the prepolymer solution, stirred for 30min, and then the reaction solution was poured into a polytetrafluoroethylene mold and vacuum-dried at 80°C for 12h to obtain a polyurethane film PU1 with an NCO / OH ratio of 1.2:1.
[0040] The tensile strength of the prepared PU1 film is 10.6MPa, and the elongation at break is 665%. The degradation rate of the PU1 film in a 2mol / L phosphoric acid / ethanol solution at 50°C is 100%, and the mass loss after six weeks of enzymatic hydrolysis is 9.88%. The biocompatibility of the PU1 film was evaluated by the CCK-8 method. After L929 cells were directly inoculated on the surface of the film and co-cultured for 24h, 48h and 72h, their cell proliferation rates (RGR) were 98.15%, 98.29% and 98.30%, respectively. The shape fixation rate (RGR) of the PU1 film at 55°C was 100%. f ) and shape recovery rate (R r ) were 88.7% and 50.3% respectively.
[0041] Example 2
[0042] 4g of hydroxyl-terminated poly (1,4-butylene adipate) (PBA) with a number average molecular weight of 2000 and 0.30g of isosorbide (ISO) were added to a three-necked flask with a stirrer, heated to 60°C, and vacuum-dried for 40min under stirring. Then, 1.2g of hexamethylene diisocyanate (HDI) dissolved in N, N-dimethylformamide (DMF) was added to the mixture, and the mixture was heated to 120°C and continued to react for 10h. At the same time, a certain amount of N, N-dimethylformamide (DMF) was added to adjust the viscosity of the system to form a prepolymer. 0.3g of hydroxyethyl hexahydro-s-triazine (HT) was added to the prepolymer solution, stirred for 30min, and then the reaction solution was poured into a polytetrafluoroethylene mold and vacuum-dried at 80°C for 12h to obtain a polyurethane film PU2 with an NCO / OH ratio of 1.2:1.
[0043] The tensile strength of the prepared PU2 film is 25.7MPa, and the elongation at break is 860%. The degradation rate of the PU2 film in a 2mol / L phosphoric acid / ethanol solution at 50°C is 100%, and the mass loss after six weeks of enzymatic hydrolysis is 12.98%. The biocompatibility of the PU2 film was evaluated by the CCK-8 method. After L929 cells were directly inoculated on the surface of the film and co-cultured for 24h, 48h and 72h, their cell proliferation rates (RGR) were 98.27%, 98.38% and 98.22%, respectively. The shape fixation rate (RGR) of the PU2 film at 55°C f ) and shape recovery rate (R r ) were 94.8% and 84.8% respectively.
[0044] Example 3
[0045] 8g of hydroxyl-terminated poly (1,4-butylene adipate) (PBA) with a number average molecular weight of 3000 and 0.30g of isosorbide (ISO) were added to a three-necked flask with a stirrer, heated to 60°C, and vacuum-dried for 40min under stirring. Then, 1.2g of hexamethylene diisocyanate (HDI) dissolved in N, N-dimethylacetamide (DMAc) was added to the mixture, and the mixture was heated to 120°C and continued to react for 10h. At the same time, a certain amount of N, N-dimethylacetamide (DMAc) was added to adjust the viscosity of the system to form a prepolymer. 0.3g of hydroxyethyl hexahydro-s-triazine (HT) was added to the prepolymer solution, stirred for 30min, and then the reaction solution was poured into a polytetrafluoroethylene mold and vacuum-dried at 80°C for 12h to obtain a polyurethane film PU3 with an NCO / OH ratio of 1.2:1.
[0046] The tensile strength of the prepared PU3 film is 18.9MPa, and the elongation at break is 978%. The degradation rate of the PU3 film in a 2mol / L phosphoric acid / ethanol solution at 50°C is 100%, and the mass loss after six weeks of enzymatic hydrolysis is 49.95%. The biocompatibility of the PU3 film was evaluated by the CCK-8 method. After L929 cells were directly inoculated on the surface of the film and co-cultured for 24h, 48h and 72h, their cell proliferation rates (RGR) were 98.30%, 98.37% and 98.33%, respectively. The shape fixation rate (RGR) of the PU3 film at 55°C was 100%. f ) and shape recovery rate (R r ) were 95.1% and 87.5% respectively.
[0047] Example 4
[0048] 2g of hydroxyl-terminated poly (1,4-butylene adipate) (PBA) with a number average molecular weight of 2000 and 1g of 1000 and 0.30g of isosorbide (ISO) were added to a three-necked flask with a stirrer, heated to 60°C, and vacuum-dried for 40 minutes under stirring. Then, 1.2g of hexamethylene diisocyanate (HDI) dissolved in N-methylpyrrolidone (NMP) was added to the mixture, and the mixture was heated to 120°C and continued to react for 10 hours. At the same time, a certain amount of N-methylpyrrolidone (NMP) was added to adjust the viscosity of the system to form a prepolymer. 0.3g of hydroxyethyl hexahydro-s-triazine (HT) was added to the prepolymer solution, stirred for 30 minutes, and then the reaction solution was poured into a polytetrafluoroethylene mold and vacuum-dried at 100°C for 12 hours to obtain a polyurethane film PU12 with an NCO / OH ratio of 1.2:1.
[0049] The tensile strength of the prepared PU12 film is 16.6MPa, and the elongation at break is 718%. The degradation rate of the PU12 film in a 2mol / L phosphoric acid / ethanol solution at 50°C is 100%, and the mass loss after six weeks of enzymatic hydrolysis is 10.43%. The biocompatibility of the PU12 film was evaluated by the CCK-8 method. After L929 cells were directly inoculated on the surface of the film and co-cultured for 24h, 48h and 72h, their cell proliferation rates (RGR) were 98.21%, 98.30% and 98.34%, respectively. The shape fixation rate (RGR) of the PU12 film at 55°C was 100%. f ) and shape recovery rate (R r ) were 95.4% and 69.7% respectively.
[0050] Example 5
[0051] 2g of hydroxyl-terminated poly (1,4-butylene adipate) (PBA) with a number average molecular weight of 2000 and 4g of hydroxyl-terminated poly (1,4-butylene adipate) (PBA) with a number average molecular weight of 3000 and 0.30g of isosorbide (ISO) were added to a three-necked flask with a stirrer, heated to 60°C, and vacuum-dried for 40 minutes under stirring. Then, 1.2g of hexamethylene diisocyanate (HDI) dissolved in N, N-dimethylformamide (DMF) was added to the mixture, and the mixture was heated to 120°C and continued to react for 10 hours. At the same time, a certain amount of N, N-dimethylformamide (DMF) was added to adjust the viscosity of the system to form a prepolymer. 0.3g of hydroxyethyl hexahydro-s-triazine (HT) was added to the prepolymer solution, stirred for 30 minutes, and then the reaction solution was poured into a polytetrafluoroethylene mold and vacuum-dried at 80°C for 12 hours to obtain a polyurethane film PU23 with an NCO / OH ratio of 1.2:1.
[0052] The tensile strength of the prepared PU23 film is 22.9MPa, and the elongation at break is 875%. The degradation rate of the PU23 film in a 2mol / L phosphoric acid / ethanol solution at 50°C is 100%, and the mass loss after six weeks of enzymatic hydrolysis is 18.89%. The biocompatibility of the PU23 film was evaluated by the CCK-8 method. After L929 cells were directly inoculated on the surface of the film and co-cultured for 24h, 48h and 72h, their cell proliferation rates (RGR) were 98.17%, 98.31% and 98.30%, respectively. The shape fixation rate (RGR) of the PU23 film at 55°C was 100%. f ) and shape recovery rate (R r ) were 95.7% and 85.1% respectively.
[0053] Example 6
[0054] 1g of polyethylene glycol (PEG) with a number average molecular weight of 1000, 1g of polylactic acid (PLA) with a number average molecular weight of 1000 and 0.30g of isosorbide (ISO) were added to a three-necked flask with a stirrer, heated to 60°C, and vacuum-dried for 40 minutes under stirring. Then, 1.3g of toluene diisocyanate (TDI) dissolved in tetrahydrofuran (THF) was added to the mixture, and the mixture was heated to 120°C and continued to react for 10 hours. At the same time, a certain amount of tetrahydrofuran (THF) was added to adjust the viscosity of the system to form a prepolymer. 0.3g of hydroxyethyl hexahydro-s-triazine (HT) was added to the prepolymer solution, stirred for 30 minutes, and then the reaction solution was poured into a polytetrafluoroethylene mold and vacuum-dried at 40°C for 12 hours to obtain a polyurethane film PU6 with an NCO / OH ratio of 1.2:1.
[0055] The tensile strength of the prepared PU6 film is 19.4MPa, and the elongation at break is 889%. The degradation rate of the PU6 film in a 2mol / L phosphoric acid / ethanol solution at 50°C is 100%, and the mass loss after six weeks of enzymatic hydrolysis is 24.30%. The biocompatibility of the PU6 film was evaluated by the CCK-8 method. After L929 cells were directly inoculated on the surface of the film and co-cultured for 24h, 48h and 72h, their cell proliferation rates (RGR) were 98.46%, 98.50% and 98.39%, respectively. The shape fixation rate (RGR) of the PU6 film at 55°C was 100%. f ) and shape recovery rate (R r ) were 96.3% and 81.43% respectively.
[0056] Example 7
[0057] 1g of hydroxyl-terminated polybutylene succinate (PBS) with a number average molecular weight of 1000, 1g of polytetramethylene ether glycol (PTMEG) with a number average molecular weight of 1000 and 0.30g of isosorbide (ISO) were added to a three-necked flask with a stirrer, heated to 60°C, and vacuum-dried for 40 minutes under stirring. Then, 1.6g of isophordine diisocyanate (IPDI) dissolved in N, N-dimethylformamide (DMF) was added to the mixture, and the temperature was raised to 120°C for continued reaction for 10 hours. At the same time, a certain amount of N, N-dimethylformamide (DMF) was added to adjust the viscosity of the system to form a prepolymer. 0.3g of hydroxyethyl hexahydro-s-triazine (HT) was added to the prepolymer solution, stirred for reaction for 30 minutes, and then the reaction solution was poured into a polytetrafluoroethylene mold and vacuum-dried at 80°C for 12 hours to obtain a polyurethane film PU7 with an NCO / OH ratio of 1.2:1.
[0058] The tensile strength of the prepared PU7 film is 15.8MPa, and the elongation at break is 703%. The degradation rate of the PU7 film in a 2mol / L phosphoric acid / ethanol solution at 50°C is 100%, and the mass loss after six weeks of enzymatic hydrolysis is 13.34%. The biocompatibility of the PU7 film was evaluated by the CCK-8 method. After L929 cells were directly inoculated on the surface of the film and co-cultured for 24h, 48h and 72h, their cell proliferation rates (RGR) were 97.21%, 98.00% and 97.31%, respectively. The shape fixation rate (RGR) of the PU7 film at 55°C was 100%. f ) and shape recovery rate (R r ) were 89.47% and 69.36% respectively.
[0059] Example 8
[0060] 1g of hydroxyl-terminated poly(1,4-butylene adipate) (PBA) with a number average molecular weight of 1000, 1g of poly(propylene glycol) (PPG) with a number average molecular weight of 1000, and 0.30g of isosorbide (ISO) were added to a three-necked flask with a stirrer, heated to 60°C, and vacuum-dried for 40 minutes under stirring. Then, 2.6g of diphenylmethane diisocyanate (MDI) dissolved in N, N-dimethylformamide (DMF) was added to the mixture, and the mixture was heated to 120°C and continued to react for 10 hours. At the same time, a certain amount of N, N-dimethylformamide (DMF) was added to adjust the viscosity of the system to form a prepolymer. 0.3g of hydroxyethyl hexahydro-s-triazine (HT) was added to the prepolymer solution, stirred for 30 minutes, and then the reaction solution was poured into a polytetrafluoroethylene mold and vacuum-dried at 80°C for 12 hours to obtain a polyurethane film PU8 with an NCO / OH ratio of 1.2:1.
[0061] The tensile strength of the prepared PU8 film is 17.4MPa, and the elongation at break is 914%. The degradation rate of the PU8 film in a 2mol / L phosphoric acid / ethanol solution at 50°C is 100%, and the mass loss after six weeks of enzymatic hydrolysis is 19.34%. The biocompatibility of the PU7 film was evaluated by the CCK-8 method. After L929 cells were directly inoculated on the surface of the film and co-cultured for 24h, 48h and 72h, their cell proliferation rates (RGR) were 98.33%, 98.40% and 98.31%, respectively. The shape fixation rate (RGR) of the PU8 film at 55°C was 100%. f ) and shape recovery rate (R r ) were 90.47% and 74.36% respectively.
[0062] Examples 1-8 show that polyurethanes containing hexahydrotriazine structures and polyester and polyether segments all have good dual degradability, biocompatibility and shape memory function.
[0063] See also Figure 1 The polyurethane films prepared in Examples 1-5 contain hexahydrotriazine rings and biodegradable aliphatic polyester straight chains, wherein a microphase separation structure is easily generated due to the incompatibility of the soft and hard segments unique to polyurethane. Polybutylene adipate-1,4-diol ester, as a soft segment in the polyurethane material, can give the material excellent mechanical strength, organic solvent resistance and heat resistance, while also showing high crystallinity, affecting the interaction between molecular segments. The shape memory behavior, strength and toughness of the elastomer can be adjusted by adjusting the ratio of the soft and hard segments in the polyurethane structure. In addition, the elastomer can be quickly and completely degraded in an acidic environment due to the acid-sensitive hexahydrotriazine ring contained in the structure.
[0064] See also Figure 2 The molecular weight of different soft segments of polyurethane films was characterized by ATR-FTIR at 3320 cm -1The signal at 1160 cm corresponds to the NH stretching vibration peak in carbamate. -1 The peaks at 2943 and 2863 cm -1 The absorption peak at 1726cm is caused by the CH stretching vibration of the methyl or methylene components. -1 The C=O stretching vibration peak of the ester bond in carbamate appears. The infrared spectra of polyurethane films with different molecular weight soft segments confirm the successful synthesis of polyurethane.
[0065] See also Figure 3 Taking the polyurethane film prepared in Example 2 as an example, its tensile strength is 25.7 MPa and its elongation at break is 860%. It can lift a weight that is about 20,000 times its own weight, indicating its excellent mechanical properties.
[0066] See also Figure 4 , taking the polyurethane film prepared in Example 3 as an example, the sample is first heated to 55°C. At this time, the soft segment of the polyurethane film is amorphous, and the crystalline region of its internal structure can be reshaped to a certain extent, and the molecular chain is rearranged. The sample is wrapped on a cylindrical glass rod to make a spirally twisted spline, and the hard segment serves as a frame to maintain its original shape; then it is placed at a low temperature. Due to the temperature reduction and deformation-induced molecular chain orientation, the soft segment of the polyurethane film undergoes a transition from a highly elastic state to a glassy state, and the movement of the molecular chain is restricted, resulting in a temporary shape fixation. The sample is heated to 55°C again. The temperature increase causes the crystals of the soft segment to melt and the stress is released, so the spline can return to its original shape. After three cycles of spiral twisting, the sample can return to its original shape, indicating that the material has excellent shape memory function.
[0067] See also Figure 5 Taking the polyurethane film prepared in Example 2 as an example, L929 cells were directly inoculated on the surface of the prepared polyurethane film and co-cultured for a period of time to evaluate the cytotoxicity of the material. It can be seen that at different culture times, the cells are evenly distributed and a healthy spindle-shaped morphology can be observed. This shows that the prepared film material has excellent biocompatibility.
[0068] See also Figure 6 Five groups of polyurethane films with different proportions were placed in 2 mol / L phosphoric acid / ethanol solution for degradation experiments, and it was found that they could all be completely degraded at room temperature.
[0069] See also Figure 7Five groups of polyurethane films with different proportions were immersed in a 2mol / L phosphoric acid / ethanol solution at room temperature for acid hydrolysis. Due to the damage to the membrane surface caused by six weeks of enzymatic hydrolysis, some gaps and holes appeared on the surface of the material, which promoted the acid hydrolysis solution to penetrate into the molecular chain and cause degradation. Therefore, all five groups of samples were able to achieve complete degradation in a relatively short time.
[0070] The above content is a further detailed description of the present invention in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, they can also make several substitutions or modifications to these described embodiments without departing from the concept of the present invention, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention.
Claims
1. A polyurethane material with shape memory function, biocompatibility and degradability, characterized in that: The polyurethane material contains a degradable hexahydrotriazine ring and a linear polyether or polyester structure. The hexahydrotriazine ring and the polyester give the polyurethane good degradability, and the polyether or polyester soft segment gives the polyurethane good shape memory function and biocompatibility. The strength and toughness of the polyurethane are regulated by the soft segment structure and molecular weight, and the ratio of soft and hard segments. The synthesis reaction process is as follows.
2. A method for preparing a polyurethane material having shape memory function, biocompatibility and degradability as claimed in claim 1, characterized in that: The following steps are involved: (1) taking a certain amount of isosorbide and hydroxyl-terminated polyether or polyester polyol, placing them in a three-necked flask, heating and melting them under a nitrogen atmosphere, and uniformly mixing them, adding a diisocyanate monomer dissolved in a solvent to the mixed liquid, reacting to obtain a viscous liquid, and adding an appropriate amount of solvent to control the viscosity of the reaction system; (2) adding hydroxyethyl hexahydro-s-triazine to the polymerization system of step (1), stirring and mixing, and then pouring the reaction mixture into a polytetrafluoroethylene mold to level it; (3) placing the mold in an oven to volatilize the solvent and solidify the mold to obtain a polyurethane material having shape memory function, biocompatibility and degradability.
3. The method for preparing a polyurethane material having shape memory function, biocompatibility and degradability as claimed in claim 2, characterized in that: The hydroxyl-terminated polyether or polyester polyol described in step (1) includes one or more of hydroxyl-terminated poly(1,4-butylene adipate), polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol, poly(butylene succinate), and polylactic acid.
4. The method for preparing a polyurethane material having shape memory function, biocompatibility and degradability as claimed in claim 2, characterized in that: The diisocyanate described in step (1) includes one or more of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate.
5. The method for preparing a polyurethane material having shape memory function, biocompatibility and degradability as claimed in claim 2, characterized in that: In step (1), the group ratio NCO:OH is 1.2:
1.
6. The method for preparing a polyurethane material having shape memory function, biocompatibility and degradability as claimed in claim 2, characterized in that: The solvent described in step (1) includes one or more of tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.
7. The method for preparing a polyurethane material having shape memory function, biocompatibility and degradability as claimed in claim 2, characterized in that: The conditions for the reaction of adding diisocyanate monomer in step (1) are to react at a temperature of 120° C. for 10 hours.
8. The method for preparing a polyurethane material having shape memory function, biocompatibility and degradability as claimed in claim 2, characterized in that: The stirring and mixing time in step (2) is 30 minutes.
9. The method for preparing a polyurethane material having shape memory function, biocompatibility and degradability as claimed in claim 2, characterized in that: The temperature for solvent volatilization and solidification in step (3) is 40-100°C.
10. The method for preparing a polyurethane material having shape memory function, biocompatibility and degradability as claimed in claim 2, characterized in that: The curing time in step (3) is 12 hours.
Citation Information
Patent Citations
Degradable polyurethane material with high mechanical property and synthesis method thereof
CN118878782A
Process for the production of hot melt adhesives having a low emission of monomeric isocyanates
CN113316601A
Degradable bio-based thermosetting resin containing isosorbide structure and preparation method thereof
CN113429535A
Quercetin-based degradable thermosetting polyurethane and preparation method thereof
CN115505085A
Functional elastomer and application
CN117384350A
Cited By
Preparation method of high-frequency flexible copper-clad plate
CN121038113A
Degradable wall fixing agent for tectonic coal seam as well as preparation method and application of degradable wall fixing agent
CN122541673A